2000
DOI: 10.1177/172460080001500405
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy and Angiogenesis in Advanced Cancer: Vascular Endothelial Growth Factor (VEGF) Decline as Predictor of Disease Control during Taxol Therapy in Metastatic Breast Cancer

Abstract: Angiogenesis is essential for tumor growth. Since vascular endothelial growth factor (VEGF) represents the main angiogenic factor, the control of VEGF secretion could constitute the most important mechanism to achieve the inhibition of angiogenesis-related processes. High blood concentrations have been proven to correlate with poor prognosis in advanced cancer. In experimental conditions, chemotherapeutic agents such as taxol appeared to inhibit VEGF-induced angiogenesis, while at present there are no data abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 7 publications
1
21
0
1
Order By: Relevance
“…Currently, the prediction of survival for patients with advanced breast cancer is often inaccurate. The accumulating evidence indicated that the pretreatment serum VEGF level could have the predictive potential (Shivakumar et al 2009;Karayiannakis et al 2003;Dudek and Mahaseth 2005;Lissoni et al 2000). This study not only confirmed the association of pretreatment serum VEGF level with patient survival (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Currently, the prediction of survival for patients with advanced breast cancer is often inaccurate. The accumulating evidence indicated that the pretreatment serum VEGF level could have the predictive potential (Shivakumar et al 2009;Karayiannakis et al 2003;Dudek and Mahaseth 2005;Lissoni et al 2000). This study not only confirmed the association of pretreatment serum VEGF level with patient survival (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies have confirmed the importance of socalled metronomic chemotherapy in preclinical models (Colleoni et al 2002). However, the conclusions on the impact of system chemotherapy on secretion of angiogenic factors from tumor and/or other cells are discordant (Tas et al 2008;Lissoni et al 2000). This work observed the changes of serum VEGF and ES levels during system chemotherapy for patients with advanced breast cancer and assessed their value in predictive and prognostic judgment.…”
Section: Introductionmentioning
confidence: 65%
“…However, other studies seem to suggest no interactions between HER2 status and taxane therapy (11, 12). Similar conflicting results were observed for other biomarkers such as the apoptotic index (9), p53 (12, 13), proliferation markers (14), and angiogenic-related markers (15,16). Thus, markers that help predict whether a patient might benefit more from a taxane-based than from an anthracycline-based regimen are clearly needed.…”
mentioning
confidence: 65%
“…The discovery of reliable markers may indeed allow the optimization of MTA dosing and the combination with other anti-angiogenic agents. Potential approaches to evaluate the efficacy of anti-vascular therapies are tumour blood flow assessed by new imaging techniques, serum or urine pro-and anti-angiogenic cytokine profiles, soluble vascular cell adhesion molecule (sVCAM) and soluble intercellular adhesion molecule (sICAM) [162,214,241,258]. Many of these activators or inhibitors of angiogenesis are soluble proteins, whose circulating levels could reflect the overall angiogenic activity of the tumour.…”
Section: Prediction Of Efficacymentioning
confidence: 99%